Antimicrobial properties in nanoparticles synthesized by biogenic route (LACCEI, 2024)
Nanomaterials (metals and metal oxides) synthesized by the green route, a method known as “biogenic” synthesis, have a wide field of applicability, highlighting their antimicrobial activity. Therefore, this meta-analysis aims to study the antimicrobial potential of nanoparticles synthesized by biogenic route. The PRISMA methodology was applied in addition to different inclusion and exclusion criteria (language, periodicity, accessibility, relative importance), obtaining a total of 40 investigations. The research concludes the efficient applicability of silver (NPs Ag), iron oxide (FeO NPs) and zinc oxide (ZnO NPs) nanoparticles as antimicrobial agents. Likewise, with a smaller size of nanostructures, efficient inhibitions are obtained, so its potential depends on the dimensions of the nanoparticle. Finally, it was possible to observe that the size of the nanomaterial depends directly on the reducer and precursor, however, it is recommended to expand the investigation, since conclusive results were not obtained at this point.